Running Behind “POPO”—Impact of Predictors of Poor Outcome for Treatment Stratification in Pediatric Crohn's Disease - de Laffolie, Jan; Zimmer, Klaus-Peter; Sohrabi, Keywan; Hauer, Almuthe Christina (Frontiers in Medicine, 2021)
Background and aims - Intensifying therapy for Pediatric Crohn’s Disease (CD) by early use of immunomodulators and biologics has been proposed for cases in which predictors of poor outcome (POPO) were present. We investigated therapy stratifying potential comparing POPO-positive and -negative CD patients from CEDATA-GPGE®, a German-Austrian Registry for Pediatric Inflammatory Bowel disease. Methods - CD patients (1-18 years) registered in CEDATA-GPGE® (2004-2018) within three months of diagnosis and at least two follow-up visits were included. Disease course and treatments over time were analysed regarding positivity of POPO criteria and test statistical properties. Results - 709/1084 patients included had at least one POPO criterion (65.4%): 177 patients (16.3%) had persistent disease (POPO2), 581 (53.6%) extensive disease (POPO3), 21 (1.9%) severe growth retardation POPO4, 47 (4.3%) stricturing/penetrating disease (POPO6) and 122 (11.3%) perianal disease (POPO7). Patients with persistent disease differed significantly in lack of sustained remission >1 year (Odd Ratio (OR) 1.49 [1.07-2.07], p=0.02), patients with initial growth failure in growth failure at end of observation (OR 51.16 [19.89-131.62], p<0.0001), patients with stricturing and penetrating disease as well as perianal disease in need for surgery (OR 17.76 [9.39-33.58], p <0.001; OR 2.56 [1.58-4.15], p<0.001, respectively). Positive Predictive Value for lack of sustained remission was >60% for patients with initial growth failure, persistent or stricturing/penetrating disease. Conclusion - Predictors of poor outcome with complicated courses of disease were common in CEDATA-GPGE®. An early intensified approach for paediatric CD patients with POPO-positivity (POPO2-4, 6-7) should be considered, because they have an increased risk to fare poorly.